2015
DOI: 10.2514/1.j053637
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-Roughness-Element-Enhanced Swept-Wing Natural Laminar Flow at High Reynolds Numbers

Abstract: Nonlinear parabolized stability equations and secondary-instability analyses are used to provide a computational assessment of the potential use of the discrete-roughness-element technology for extending swept-wing natural laminar flow at chord Reynolds numbers relevant to transport aircraft. Computations performed for the boundary layer on a natural-laminar-flow airfoil with a leading-edge sweep angle of 34.6 deg, freestream Mach number of 0.75, and chord Reynolds numbers of 17 × 10 6 , 24 × 10 6 , and 30 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…On the other hand, the peak mean flow correction amplitudes for both stationary and traveling modes were found to be comparable to each other. These features of the nonlinear evolution of isolated traveling and stationary crossflow disturbances are similar to those reported by Malik et al 30 for a different airfoil configuration as well as to the findings of Wassermann and Kloker 8 for a boundary-layer flow past a flat plate that is subjected to a favorable pressure gradient. NPSE computations of traveling crossflow mode 2 also showed that nonlinearity caused the amplitude of the fundamental mode to evolve in an oscillatory manner following the initial rise to the first peak, the latter representing the global maximum of the fundamental mode amplitude.…”
Section: Numerical Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, the peak mean flow correction amplitudes for both stationary and traveling modes were found to be comparable to each other. These features of the nonlinear evolution of isolated traveling and stationary crossflow disturbances are similar to those reported by Malik et al 30 for a different airfoil configuration as well as to the findings of Wassermann and Kloker 8 for a boundary-layer flow past a flat plate that is subjected to a favorable pressure gradient. NPSE computations of traveling crossflow mode 2 also showed that nonlinearity caused the amplitude of the fundamental mode to evolve in an oscillatory manner following the initial rise to the first peak, the latter representing the global maximum of the fundamental mode amplitude.…”
Section: Numerical Resultssupporting
confidence: 89%
“…Experimental flow visualizations have confirmed that the transition front associated with traveling crossflow disturbances is indeed smooth in nature. 30 The mean shear evolution in Fig. 11(b) indicates a rapid rise in the near-wall mean velocity at x/c ≈ 0.39, indicating the onset of transition location.…”
Section: B Breakdown Of Secondary Instabilitymentioning
confidence: 92%
“…For the Mack mode, ultrasonically absorptive coatings or wavy wall are usually used (see overview [22]). For the crossflow modes, plasma actuators [23], localized suction [24] and discrete-roughness-elements [25] are possible options. Consequently, the transition routine in experiments needs to be further confirmed preferably with more information inside the boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…To further assess the potential capability of the DRE concept to control swept-wing transition at transonic Mach numbers and substantially higher chord Reynolds numbers than previous applications, a high-Reynolds-number flight experiment, referred to as the Subsonic Aircraft Roughness Glove Experiment (SARGE), was recently initiated to design high-Reynolds-number NLF wing configurations with a maximum possible chord Reynolds number approaching Re cs = 30 × 10 6 . 11 For such configurations, Malik et al 12 and Li et al 13 conducted a computational assessment of the DRE concept using nonlinear parabolized stability equations (PSE) and secondary-instability analysis, with the particular conditions used for the assessment consisting of a freestream Mach number of 0.75 and chord Reynolds numbers of 17 × 10 6 , 24 × 10 6 , and 30 × 10 6 . The computations demonstrated that DREs can suppress dominant boundary-layer disturbances at the chosen Reynolds numbers.…”
Section: Introductionmentioning
confidence: 99%
“…To complement the stability analysis by Malik et al 12 and Li et al 13 as well as to provide computational assessment of the DRE technology for potential application to transport aircraft, the current paper studies the receptivity to roughness using DNS of compressible Navier-Stokes equations for a spatially developing transonic 3-D boundary layer over a realistic NLF wing configuration at Reynolds numbers relevant to transport aircraft. DNS results are analyzed to determine the initial amplitude and mode shapes of induced stationary crossflow modes as well as to shed light on the relation of the modal amplitudes to the size and distribution of roughness.…”
Section: Introductionmentioning
confidence: 99%